2018
DOI: 10.1103/physrevlett.121.165301
|View full text |Cite
|
Sign up to set email alerts
|

Diagrammatic Monte Carlo Approach to Angular Momentum in Quantum Many-Particle Systems

Abstract: We introduce a Diagrammatic Monte Carlo (DiagMC) approach to angular momentum properties of quantum many-particle systems possessing a macroscopic number of degrees of freedom. The treatment is based on a diagrammatic expansion that merges the usual Feynman diagrams with the angular momentum diagrams known from atomic and nuclear structure theory, thereby incorporating the non-Abelian algebra inherent to quantum rotations. Our approach is applicable at arbitrary coupling, is free of systematic errors and of fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 72 publications
1
7
0
1
Order By: Relevance
“…A similar ansatz has been previously shown to provide a good approximation to the energies of polarons 42 and angulons 43 , even far beyond the weak-coupling regime considered in this paper. In Eq.…”
Section: The Microscopic Modelsupporting
confidence: 53%
“…A similar ansatz has been previously shown to provide a good approximation to the energies of polarons 42 and angulons 43 , even far beyond the weak-coupling regime considered in this paper. In Eq.…”
Section: The Microscopic Modelsupporting
confidence: 53%
“…In contrast eq. (25) shows that the typical transition rates for a rotating molecule are bigger by a factor ξ/r 0 . This may raise concerns if angulons can be observed at all.…”
Section: A Single-phonon Rates and Angulon Stabilitymentioning
confidence: 97%
“…Recently the concept of a polaron was extended to impurities with a more complex structure such as a molecule. It was shown that the coupling of rotation to collective excitations of a surrounding BEC can give rise to a new type of quasi-particles termed angulons [21][22][23][24][25]. In the present paper we discuss the cooling dynamics of the rotational degrees of freedom of a single, diatomic molecule immersed in a three-dimensional (3D) Bose-Einstein condensate, see Fig.…”
Section: Introductionmentioning
confidence: 98%
“…(2). They involve perturbations on the top of a microscopic deformation of the helium bath, i. e. an infinite number of bosonic excitations [25][26][27] . In the course of the paper, however, we aim to demonstrate that the solutions including up to triple excitations are able to catch changes in molecular spectra for broad range of species measured in helium.…”
Section: A the Angulon Hamiltonianmentioning
confidence: 99%